1998
DOI: 10.1136/gut.43.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-kininogen system activation and bradykinin (B2) receptors in indomethacin induced enterocolitis in genetically susceptible Lewis rats

Abstract: Background-The plasma kallikrein-kinin (K-K) system is activated in acute and chronic relapsing intestinal inflammation induced in Lewis rats by intramural injection of exogenous bacterial components. Aims-To determine whether this eVect is model specific, K-K system activation was investigated in a modified indomethacin induced enterocolitis model, as well as bradykinin 2 (B2) receptor distribution in the normal and acutely inflamed intestine. Methods-Lewis rats injected with daily sublethal doses of indometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…In our models of inflammatory arthritis and enterocolitis induced by proteoglycan-polysaccharide (PG-APS), activation of plasma kallikrein was documented in the genetically susceptible Lewis rat but not in the resistant Buffalo rat (12). This activation is not specific for PG-APS since it can be induced by indomethacin in Lewis rats (23). A selective plasma kallikrein inhibitor has been shown to attenuate acute (19) and chronic (22) enterocolitis in the Lewis rat at low concentrations, which selectively inhibits plasma kallikrein.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In our models of inflammatory arthritis and enterocolitis induced by proteoglycan-polysaccharide (PG-APS), activation of plasma kallikrein was documented in the genetically susceptible Lewis rat but not in the resistant Buffalo rat (12). This activation is not specific for PG-APS since it can be induced by indomethacin in Lewis rats (23). A selective plasma kallikrein inhibitor has been shown to attenuate acute (19) and chronic (22) enterocolitis in the Lewis rat at low concentrations, which selectively inhibits plasma kallikrein.…”
mentioning
confidence: 86%
“…20). Agents that block BK receptors also modulate experimental inflammatory arthritis induced by PG-APS (23,24). Recently, we have shown that experimental enterocolitis is 60% inhibited in rats deficient in HK and LK in a Lewis genetic background (8a).…”
mentioning
confidence: 99%
“…Enhanced excitability in both populations of submucosal neurons by BK is a mechanistic explanation for reports of stimulated mucosal secretion during exposure to BK (Kachur et al, 1987;Gaginella and Kachur, 1989). The pathophysiological significance of the neuronal actions of BK can therefore be related to the secretory diarrhea associated with intestinal inflammatory states in which the BK levels increase and the BK B 2 receptor is overexpressed (Stadnicki et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the involvement of the kallikrein-kinin system in the development of experimental IBD models that mimic human Crohn's disease was also reported (8,9,35). Although it was reported that the activation of the plasma kallikrein-kinin system was evaluated from the consumption of plasma prekallikrein and high-molecularweight kininogen (8,35), the actual contribution of kinins to enterocolitis should be tested using adequate biological and pharmacological approaches (36). It is well known that kinins are very readily degraded to the inactive peptides (37) and that the above precursor proteins are degraded to the small molecules without generating kinins in some inflammatory situations (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, in spite of the potent proinflammatory activity of kinins, the involvement of the kallikrein-kinin system in the development of experimental enterocolitis (8,9,22) and colitis (4) has been demonstrated, but the number of reports is limited. In a model of granulomatous enterocolitis induced in a genetically susceptive strain of Lewis rats by peptidoglycan-polysaccharide polymers isolated from group A streptococci, the activation of the plasma kallikrein kinin system was presumed to have occurred, because of the consumption of the precursor proteins plasma prekallikrein and high-molecular-weight kininogen (9, 23 -25).…”
mentioning
confidence: 99%